A REVIEW OF HAPTIC FEEDBACK IN VIRTUAL REALITY FOR MANUFACTURING INDUSTRY - Aziz, Faieza Abdul; Mousavi, Maryam (Journal of Mechanical Engineering, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This paper discusses the application of haptic feedback in Virtual Reality to enhance user performance in manufacturing industry. Haptic interfaces have the potential to enhance communication and interaction via the computer enabling affective expressive interpersonal communication and enriching interaction by haptic feedback. The aim of this study was to investigate and develop a better understanding of using haptic feedback in manufacturing. Keywords: Virtual Reality, haptic, manufacturing doi: 10.3329/jme.v40i1.3476 Journal of Mechanical Engineering, Vol. ME40, No. 1, June 2009 68-71